Determinants of Financial Stress of Indian Banks: Hierarchical Bayesian Panel Data Modelling. Issue 2 (September 2018) - Kumar, Nitin; Shrivastava, Arvind; Singh, D. P.; Kumar, Purnendu
The study examines factors influencing non-performing loans (NPLs) for Indian banks. The analysis contributes by including restructured advances also in addition to standard measures of asset quality that provides comprehensive picture of pressure on banks' balance sheet. Moreover, Bayesian technique with multivariate t -distributed prior is applied for robust estimation. Utilizing quarterly dataset from 2005 to 2015, strong persistence of bad assets is clearly evident. Bank-specific characteristics such as growth of advances, profitability and net interest margin are significant determinants. Among macro-factors, high growth rate is having retarding impact on bad assets. Moreover, ownership effect is having differential behaviour with state-owned banks being most vulnerable. JEL: G21, C11, C23